2006
DOI: 10.1038/sj.ijo.0803393
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic polypeptide in obese children before and after weight loss

Abstract: Objective: Little is known concerning pancreatic polypeptide (PP) in weight loss and in childhood obesity. Methods: Fasting PP, leptin and insulin concentrations were determined in 38 obese children and compared with 35 lean children of the same age, gender and pubertal stage. Furthermore, changes of PP concentrations over a 1-year period were analyzed in the obese children participating in a weight loss intervention program. Results: Obese children had significantly (Po0.01) lower PP, and higher leptin and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 38 publications
(52 reference statements)
1
28
0
Order By: Relevance
“…25 Yet, the changes in PP concentrations did not significantly correlate to changes of insulin and leptin concentrations. 25 Amylin is a 37-amino acid polypeptide synthesized and released together with insulin by the pancreatic beta cells 15 Reinehr et al, 16 Verdich et al, 17 24 Laimer et al, 28 in response to nutritional input and contributes to glycemic and appetite control (Table). 26,76 Amylin is a satiety peptide, causing a reduction of the meal size and inhibition of gastric emptying.…”
Section: Pancreatic Hormones and Peptidesmentioning
confidence: 95%
See 3 more Smart Citations
“…25 Yet, the changes in PP concentrations did not significantly correlate to changes of insulin and leptin concentrations. 25 Amylin is a 37-amino acid polypeptide synthesized and released together with insulin by the pancreatic beta cells 15 Reinehr et al, 16 Verdich et al, 17 24 Laimer et al, 28 in response to nutritional input and contributes to glycemic and appetite control (Table). 26,76 Amylin is a satiety peptide, causing a reduction of the meal size and inhibition of gastric emptying.…”
Section: Pancreatic Hormones and Peptidesmentioning
confidence: 95%
“…75 Changes in PP levels and their relation to the anorexigenic hormones insulin and leptin were studied in Obeldicks. 25 At baseline, obese subjects had lower PP concentrations compared with lean controls. 25 Following lifestyle intervention, PP concentrations significantly increased and tended to normalize in the children who achieved substantial weight loss in comparison with children who did not lose weight.…”
Section: Pancreatic Hormones and Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…PPY administration in humans also leads to a sustained decrease in both appetite and food intake [33]. However, it has been demonstrated that low levels of PPY in obese children normalise after weight loss, suggesting that levels of PPY may reflect the overweight status rather than cause it [34]. These observations indicate that PPY may be involved in the regulation of energy balance and possibly the aetiology of obesity.…”
Section: Introductionmentioning
confidence: 99%